(untitled) (Journal of Economic Research & Business Administration, 2018)
The article deals with the economic aspects of the integration of states in the format of the EAEC. Based on the analysis of legal documents, indicators of foreign economic activity, a conclusion is made about the political expediency of integrating emerging markets. Attention is drawn to the fact that the member states of the Eurasian Economic Union are striving for integration both at the regional and international levels. Efforts are being made to expand the Free Trade Zones – with Serbia, Iran, Israel, India, etc. Despite certain obstacles, it is concluded that it is too early to speak about the seven-mile integration path of the EAPC member countries. The problems that prevent the development of integration processes within the framework of the EAEC are revealed. Among them, in particular, barriers, exemptions, restrictions, different levels of economies of states, trade conflicts. It is noted that the prospects of the integration project of the EAEC are related to the harmonization of the law of the Union and the legislations of national states, the development of a unified infrastructure policy, the expansion of the integration ties of member countries in such areas as nuclear energy, space, renewable energy sources, digital economy, overcoming political differences, etc.